Implications of Teacher Competency and Learning Models on Student Motivation and Discipline Based on SMART-PLS - Mohammad Amin Lasaiba; Arman Man Arfa (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning is a cognitive process that enables students to engage in critical thinking, interact with information, and subsequently apply their knowledge to solve issues.   The dynamic classroom approach enhances students' active learning, fosters student motivation, and promotes collaborative interactions among students, reducing conflicts and fostering discipline in both the classroom and the school. This study examines the Moving class model, teacher pedagogic competence, motivation, and learning discipline using the SmartPLS application-based Structural Equation Model (SEM). The location in this study was a state senior high school in Ambon, with samples obtained by simple random sampling of 41 students for the experimental class and 40 for the control class. The results obtained were that the validity and reliability tests on the outer model showed a value of Standardized Loading Factors (SLF) 0.7, Construct Reliability (CR) 0.5, and Average Variance Extracted (AVE) 0.5, so it was said to be valid and reliable. In contrast, in the Inner model, the dependent variable simultaneously influences learning motivation (Y) with an R Square value of 0.672 and learning discipline (Z) of 0.506, so the model is categorized as moderate. The Goodness of Fit (GoF) index shows Q square 0 and RMSE 0.05 and has predictive relevance indicating relevant exogenous latent variables. The significance test for proving the hypothesis showed that all variables had a positive and significant effect with a t-statistic 1.96 and a p-value 0.05. Limitations in this study include the arrangement of students, fluency in learning, and utilization of learning resources. As a continuation of this research, other research variables can be studied regarding personality, professionalism, and social competence and their influence on learning outcomes, self-efficacy, etcetera.